If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -5) + -6 = 24 Reorder the terms: -6(-5 + x) + -6 = 24 (-5 * -6 + x * -6) + -6 = 24 (30 + -6x) + -6 = 24 Reorder the terms: 30 + -6 + -6x = 24 Combine like terms: 30 + -6 = 24 24 + -6x = 24 Add '-24' to each side of the equation. 24 + -24 + -6x = 24 + -24 Combine like terms: 24 + -24 = 0 0 + -6x = 24 + -24 -6x = 24 + -24 Combine like terms: 24 + -24 = 0 -6x = 0 Solving -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = 0 Simplifying x = 0
| 4(x-1/2)9 | | (11+x)(16+x)=500 | | 2y-5+3y-7= | | x+3(y)+2(z)=88 | | 2/5x-2=8-13/5x | | x+3x+2x=88 | | x*x=x*x-8 | | 5r^2+42r=27 | | ln(y-3)=8 | | 4(1+2m)=2(5m+8) | | 6.7x+6=3.7x+21 | | -14x+6=-7 | | (11+x)(16+x)=324 | | 3(3n+5)=-3(-5+6n) | | 2*3x+5y=-17 | | 9b+2-(-8b+5)=8b+4 | | 2x^2-9x-8=-3x | | 3x+2x=88 | | 2*3+5y=-17 | | 9x+2-(-8x+5)=8x+4 | | 4(x+1)=2(-x-1) | | 6x^2+4=-5x | | z^2-5z-27=0 | | 4(3n-6)=-3(5-7n) | | 18p+3z-56=14-z | | 9.2x-8=2.2x+13 | | -5+5x= | | 9h^2-16=0 | | -(m-4)=-3(m-6) | | (3x+1)=(2x-8) | | C=(b+rm)(l+t) | | (x-2)*(x+5)=400 |